Comparison of organic compounds in char and soot from the combustion of biomass in boilers of various emission classes - Růžičková, Jana; Kucbel, Marek; Raclavská, Helena; Švédová, Barbora; Raclavský, Konstantin; Juchelková, Dagmar (Journal of environmental management, 2019)
The combustion of biomass in boilers of emission classes 2 and 3 produces deposits in the form of char and soot inside the combustion chamber. Char and soot differ in content of elemental carbon (EC) and organic carbon (OC) as well as in the content of organic compounds. Deposits from boilers of emission class 2 contain higher amounts of OC and EC than those from boilers of emission class 3. The only exception is deposits formed by the combustion of briquettes from hardwood in boilers of emission class 3 that contained approximately by up to 60 percent higher amount of OC and by approx. 100% more EC than deposits from combustion in boilers of emission class 2. Deposits identified as char are characterized by dominant organic compounds derived from thermic degradation of cellulose, lignin, phytosterols, terpenes, their alteration products, and aromatic hydrocarbons. Deposits identified as soot have dominant PAHs, compounds containing oxygen (furans, benzofurans, phenols) and compounds containing aliphatic nitrogen (benzonitrile). Char from boilers of emission class 2 contains approx. by 80% more alkanes and cycloalkanes, by 80% more nitriles, by 50% more carboxyl acids, by 230% more anhydrosaccharides, phytosterols and by 180% more PAHs. These differences can be utilized for identification of burned fuel.
Keywords: uhlík; Py-GC/MS; látky znečišťující vzduch; Nitrogen; polycyklické aromatické uhlovodíky; Air Pollutants; Carbon; Biomass; Soot; Char; Residential heating; Combustion; saze; dusík; Polycyclic Aromatic Hydrocarbons; biomasa